PROSES PERANCANGAN MESIN PENEPUNG BIJI-BIJIAN DENGAN METODE VDI 2221 - Sumiyanto ,; Rudi Saputra (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT The purpose of making a grain cutting machine is to process grains into flour so that it is easy to process in various types of food. This grain cutting machine can also be used as a business field for small and medium micro. The design of this grain cutting machine uses the VDI 2221 method. Using the VDI 2221 method, there are three variations of the choice of grain cutting machines. Of the three variations of the choice of the seed-making machine , the grain is selected the third choice variation because it suits the list of the will and desire of the designer. The grain cutting machine retaining engine uses gasoline motor propulsion using a V belt transmission system. This type of crusher uses a hammer mill as a grain crusher. This grain cutting machine has dimensions of 50 x 80 x 100 cm and has wheels equipped to facilitate mobility so that it can be moved easily. The use and maintenance of the machine is easy to do. Manufacturing costs are cheap and materials are easy to obtain. Keywords : The Grains Cutting Machine, Hammer Mill, VDI Method 2221. Vbelt